Characterization and storage of eugenia klotzschiana o. Berg fruits1 - Sanches, Alex Guimarães [UNESP]; Pedrosa, Vanessa Maria Dantas [UNESP]; da Silva, Maryelle Barros [UNESP]; Fernandes, Thiago Feliph Silva [UNESP]; Teixeira, Gustavo Henrique de Almeida [UNESP] (FapUNIFESP (SciELO), 2021)
Pera-do-cerrado (Eugenia klotzschiana O. Berg) has a good appearance and adequate post-harvest shelf life. However, little information is available regarding its maturity stages. This study aimed at characterizing E. klotzschiana fruits harvested at three maturity stages (immature, physiological mature and ripe), in addition to evaluating the physical and chemical changes during storage at ambient temperature (24 ± 2 ºC and 75 % ± 5 % of RH) for up to 5 days. The ripe fruits had a higher fresh mass (98.03 g), width (5.61 cm) and ratio (5.37), and lower titratable acidity (1.27 %). In contrast, immature fruits showed a greener peel (101.32 ºh) and higher vitamin C content (11.23 mg 100 g-1). There was an increase in the fresh weight loss (3.05 %) and a decrease in the peel luminosity (67.09-57.12 L*) and vitamin C content (8.11-5.04 mg 100 g-1). However, the soluble solids (SS) values did not change during the 5 days of storage. A reduction in the titratable acidity (TA; 1.29-1.06 %) was also observed, which resulted in a higher ratio (3.81-5.84). In conclusion, E. klotzschiana fruits should be harvested ripe, as they present larger dimensions, better color, higher SS/TA (flavor) and are less acidic.
Caracterização e armazenamento de frutos de eugenia klotzschiana o. Berg
Keywords: Brazilian savanna; Myrtaceae; Native fruit; Pera-do-cerrado